On n-Tupled Coincidence Point Results in Metric Spaces. (17th March 2013) - Imdad, Mohammad; Soliman, Ahmed H.; Choudhury, Binayak S.; Das, Pradyut
Abstract : We prove some n -tupled coincidence point results whenever n is even. We give here several new definitions like n -tupled fixed point, n -tupled coincidence point, and so forth. The main result is supported with the aid of an illustrative example.